Conservative Approach to Preneoplastic Cervical Lesions in Postmenopause - VETRANO, Giuseppe; ALEANDRI, Vincenzo; CIOLLI, Paola; SCARDAMAGLIA, Paola; PACCHIAROTTI, Arianna; VERRICO, Monica; CARBONI, Simona; COROSU, Roberto (Anticancer research, 2008)
Aim: To evaluate the recurrence rate of high-grade squamous intraepithelial lesions in postmenopausal women previously submitted to laser CO 2 conization and the role of persistent oncogenic HPV types. Patients and Methods: Fifty-five patients with a cytological diagnosis of high-grade squamous intraepithelial lesions were triaged with a standard colposcopy. Hormonal replacement therapy was considered as significative in influencing cervical trophism. Vaginal smears for microbiological examination were obtained. H-R HPV test was performed by PCR. The follow-up checks including cytology, colposcopy and HVP test were performed for a minimum of 5 years. Results: Histological analysis revealed 19 CIN2 (cervical intraepithelial lesions) and 36 CIN3 lesions. The cumulative failure rate at first treatment was 14% . HPV test was positive for HPV 16 type in all patients. Forty-two patients during the follow up checks resulted negative to cytology, colposcopy and HR HPV test. At the one-year follow-up check, 7 patients revealed normal cytological and abnormal colposcopical findings and persistent positive HR HPV test. At the five-year follow-up check, 14 patients with a normal cytological smear had a recurrence of CIN2/3 and positive HR HPV test. Conclusion: In postmenopause, the correct management of H-R squamous intraepithelial lesions is still debated. However, a satisfactory follow-up is the main requirement for the conservative management. HPV typing in the follow-up is important to detect persistent types to identify women at risk of developing cervical abnormalities. The incidence of cervical neoplasia does not decrease with increasing age. Since HPV positivity predicted subsequent infection, testing postmenopausal patients for the virus may be a cost-effective method of disease prevention.